Quantitative MRI volumetry, diffusivity, cerebrovascular flow, and cranial hydrodynamics during head-down tilt and hypercapnia: the SPACECOT study - Kramer, Larry A; Hasan, Khader M; Sargsyan, Ashot E; Marshall-Goebel, Karina; Rittweger, Jörn; Donoviel, Dorit; Higashi, Saki; Mwangi, Benson; Gerlach, Darius A; Bershad, Eric M (Journal of applied physiology (1985), 2017)
To improve the pathophysiological understanding of visual changes observed in astronauts, we aimed to use quantitative MRI to measure anatomic and physiological responses during a ground-based spaceflight analog (head-down tilt, HDT) combined with increased ambient carbon dioxide (CO ). Six healthy, male subjects participated in the double-blinded, randomized crossover design study with two conditions: 26.5 h of -12° HDT with ambient air and with 0.5% CO , both followed by 2.5-h exposure to 3% CO Volume and mean diffusivity quantification of the lateral ventricle and phase-contrast flow sequences of the internal carotid arteries and cerebral aqueduct were acquired at 3 T. Compared with supine baseline, HDT (ambient air) resulted in an increase in lateral ventricular volume ( = 0.03). Cerebral blood flow, however, decreased with HDT in the presence of either ambient air or 0.5% CO ( = 0.002 and = 0.01, respectively); this was partially reversed by acute 3% CO exposure. Following HDT (ambient air), exposure to 3% CO increased aqueductal cerebral spinal fluid velocity amplitude ( = 0.01) and lateral ventricle cerebrospinal fluid (CSF) mean diffusivity ( = 0.001). We concluded that HDT causes alterations in cranial anatomy and physiology that are associated with decreased craniospinal compliance. Brief exposure to 3% CO augments CSF pulsatility within the cerebral aqueduct and lateral ventricles. Head-down tilt causes increased lateral ventricular volume and decreased cerebrovascular flow after 26.5 h. Additional short exposure to 3% ambient carbon dioxide levels causes increased cerebrovascular flow associated with increased cerebrospinal fluid pulsatility at the cerebral aqueduct. Head-down tilt with chronically elevated 0.5% ambient carbon dioxide and acutely elevated 3% ambient carbon dioxide causes increased mean diffusivity of cerebral spinal fluid within the lateral ventricles.